PERAN KOMUNIKASI FRONTLINER DALAM MENCIPTAKAN KEPUASAN INFORMASI NASABAH DI PERSEROAN TERBATAS (PT) BANK RIAU KEPULAUAN RIAU CABANG SYARIAH PEKANBARU - Ori Tivani Suhada; Nurjanah " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Frontliner communication role in the bank institution is very important. Basicly, frontliner task is to give customer an information clearly. That’s why ability of frontliner communication is very expected on this process. The purpose of this research are to know how frontliner communication role in creating customer satisfaction of information and what factors that would be the causing of creating customer satisfaction of information.This research using qualitative descriptive research method. The research is done in the company opened bank Riau Kepri Syariah branch Pekanbaru, Subject of this research are frontliner and customers. The research using purposive sampling approach to frontliner and accidental sampling to customers. Kind and data resource used are primary data and secondary data, data collecting technique used are observation, interview and documentations. Data analys technique used is Huberman and Miles interactive model, and technical examination of the validity of data used are triangulation and extension participation.The research of result showing that frontliner communication role is highly important in creating customer satisfaction of information. Point of frontliner role are as a people that analizing necessary and customer’s problem, as an information resource to customer, fullffill all the necessary of information that customer need based on prosedures applicable in the bank, and develop good relationship with the customer. Beside communication role, there are factors that give the influence to create customer satisfaction of information on the company opened Bank Riau Kepri Branch Syariah Pekanbaru, such as quality of human resources, fluent communication in any aspect, fast service kind and comfort, easyness on getting informations and also master of information about banking products.Keyword: Communication, Communication Role, and Satisfaction of Information